THE CONSTRUCTION OF MODERATION IN RELIGIOUS EDUCATION BASED ON LOCAL WISDOM - Hendi Sugianto; Muhaemin Muhaemin; Abdul Rahim Karim (Nurul Jadid University, 2024)
This research uses qualitative research methods to describe the construction of religious moderation based on local wisdom at the Pesantren Harisul Khairat. Data collection techniques in this study were carried out through observation with the type of participant observation, interviews with semi-structured interviews, and documentation studies. The data obtained was then analyzed using an interactive analysis model following to Miles and Huberman, namely data condensation, data presentation, and verification or conclusion drawing. The results showed that the construction of religious moderation education in Pesantren Khairaat applies the charismatic approach of the kyai and the rules of the Pesantren in shaping the character, discipline, and spirituality of the students at the externalization stage. The objectivation process occurs through interactions between students and their understanding of religious moderation that is institutionalized in daily practice, becoming an objective reality that is internalized by students. In the internalization stage, the Pesantren maintains values and traditions through socio-cultural adaptation, and students develop a subjective understanding of religious moderation education.